Effectiveness of the Booklet on Knowledge and Attitudes Regarding Prevention of Chronic Energy Deficiency - Shalsabila Cindy Ramadhanti; Satriani; Amiruddin; Dini Indo Virawati (Formosa Journal of Multidisciplinary Research, 2023)
There are several ways that can be done to prevent CED, one of which is through nutritional education. This research aims to determine the effectiveness of booklet media on changes in knowledge and attitudes regarding the prevention of CED in adolescent girls. The research was conducted using a quasi-experimental design with a pre-post test with control group. The sample was divided into 18 experimental groups and 18 control groups. Data analysis used the Wilcoxon and Mann Whitney tests. The research results showed that there was an increase in knowledge in the experimental group with a p-value of 0.000 and an increase in attitudes with a p-value of 0.040. There is a significant average difference between the level of knowledge (p-value = 0.029) and attitude (p-value = 0.012) between the experimental group and the control group. The booklet is effective in increasing knowledge and attitudes regarding preventing chronic energy deficiency in adolescent girls.